Clinical Profile and Management of Prosthetic Valve Thrombosis in Tertiary Cardiac Centre - Huma Naeem Tareen, Maliha Saad, Muhammad Ahsan Bashir, Tariq Memon, Iftikhar Hussain, Muhammad Rehan Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Aim: Prosthetic valve thrombosis is a potentially fatal outcome of valve replacement surgery. A proportion of patients suffer with thrombotic problems, mostly as a result of inadequate anticoagulation status and irregular INR checks. The present study aimed to investigate the clinical profile and prosthetic valve thrombosis management in tertiary cardiac centers. Patients and Methods: This prospective study was carried out on 58 prosthetic valve thrombosis patients in AFIC, Rawalpindi and Punjab Institute of Cardiology, Lahore from January 2022 to June 2022. The study protocol was approved by the institutional research and ethical committee. All the enrolled patients provided informed written consent. Patients’ demographic details, clinical profile, in-hospital complications, and outcome during one year follow-up were recorded. SPSS version 28 was used for data analysis. Results: Of the total 58 PVT patients, there were 22 (37.9%) male and 36 (62.1%) females. The overall mean age was 32.84± 8.4 years with an age range 10-65 years. About 34 (58.6%) patients had sub-therapeutic INR values during admission time whereas 28 (48.3%) patients had atrial fibrillation. Breathing difficulties was the predominant complaint in 54 (92.8%) of the patients who came within one week after the beginning of symptoms. Approximately 51 patients (88.4%) had streptokinase thrombolysis, while four required surgery. Valve thrombosis was most prevalent in 49 (84.5%) of the individuals. In-hospital mortality was 9.8% (n=6), with no significant bleeding episodes or new strokes seen. Conclusion: The present study concluded that PV thrombosis is a medical emergency associated with a high mortality rate. Low socio-economic level leads to poor adherence to anticoagulation medication. The prosthetic valve thrombosis patients had poor compliance and sub-therapeutic INR. Prosthetic valve thrombosis can be effectively treated with thrombolysis. Keywords: Prosthetic valve thrombosis, Clinical profile, Thrombosis